Occupational Context and Common Mental Disorders in Workers from the Federal Judiciary in Rio Grande do Sul, Brazil - Mayte Raya Amazarray; Gabrielle Farias Oliveira; Fernando Ribas Feijó (Revista Psicologia)
Civil servants from the Judiciary have been exposed to management models that bring risks to their mental health. Associations between the occupational context of workers from the Federal Judiciary of Rio Grande do Sul and Common Mental Disorders (CMD) were analyzed. Participants included 2,063 workers who responded to: sociodemographic and labor questionnaire, Work Context Assessment Scale, and Self-Reporting Questionnaire. We ran bivariate analyses and multivariate Poisson Regression. General prevalence of CMD was 27.2%. There was strong, positive association between work context and CMD. Workers exposed to severe work organization (WO) and severe socioprofessional relations (SR) presented 3.95-fold higher prevalence of CMD, compared to those with satisfactory WO and SR. Regarding the independent relationship between work context dimensions and CMD, associations remained strong, with prevalence up to 2.5 times higher, suggesting that the Judiciary’s work context, in critical or severe situations, can generate psychological suffering.